Design and analysis of modular pneumatic soft crawling robots - YIN Hongfei; LÜ Yuedong; SONG Xiaojuan (Jixie chuandong)
ObjectiveThe modular soft robot has high flexibility and unlimited degrees of freedom in theory, and can adapt to various complex environments and task requirements. Therefore, a kind of honeycomb soft driving unit was designed, which can be connected and composed to realize the modular driving soft robot with different functions.MethodsThe material selection and mechanical analysis of the designed imitation honeycomb soft drive unit were carried out, and a nonlinear relational model between the driving pressure and deformation in the soft drive unit was established; the validity of the model was verified by combining with the finite element simulation. Based on the imitation honeycomb soft body drive unit module, a flexible soft robot and a bidirectional bending soft robot were designed, and finite element simulations on both configurations of soft robots were conducted. Finally, the production of soft robots and test research on the modular driving of soft robots were conducted.ResultsThe simulation results show that the bidirectional bending soft robot has a larger deformation range and better bearing capacity than the flexible soft robot with the same length. The test results show that the bidirectional bending soft robot can realize the linear crawling and turning motion like worm. And the test results of two kinds of soft robot configurations are basically consistent with the simulation results.